Нагородне право: стан дослідження проблематики - Коритько, Д.Г. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Акамулируется состояние исследований о становления и развитии наградного права как самостоятельной сферы правовых норм и отношений. Показано необходимость дальнейшего научного исследования феномена государственных наград, продолжения дискуссий для дальнейшего совершенствования наградного дела, рационального использования государственных наград как инструмента правового стимулирования и государственного управления, учитывая украинский и мировой опыт в наградной политике. The author reviews research on the state and development of the law relating to the awarding as an sphere of the legal rules and relations. The author stresses the attention on the necessity of the further scientific research of the phenomenon of state awards, the continuation of discussions on the further improvementation of the law of state awards, the rational use of state awards as a tool of legal stimulation and and state management, considering Ukrainian and other states' experience in awarding politics.